1997
DOI: 10.1111/j.1151-2916.1997.tb03100.x
|View full text |Cite
|
Sign up to set email alerts
|

Shrinkage‐Free, Alumina–Glass Dental Composites via Aluminum Oxidation

Abstract: Alumina–glass composites that contain oxidized aluminum were investigated to make shrinkage‐free, all‐ceramic dental porcelain. This was achieved by control of the volume expansion and shrinkage that occur during the aluminum oxidation and densification processes. The dimensional change and strength of the alumina‐glass composites were dependent on the aluminum content and particle size. A shrinkage‐free sample with a strength of 330 MPa and transmittance of 1.21 was fabricated by using 4‐5 vol% of aluminum po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 9 publications
(9 reference statements)
0
11
0
Order By: Relevance
“…The compositions of the glasses used in glass-infiltrated ceramic composites reported in literature [34][35][36][37] are shown in Table 3, and are divided in two groups according to the type of porous ceramic preform used for glass infiltration: aluminaAl 2 O 3 (A1 to A3), or spinel-MgAl 2 O 4 (S1 to S5). The reported infiltration temperatures are also indicated in Table 3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The compositions of the glasses used in glass-infiltrated ceramic composites reported in literature [34][35][36][37] are shown in Table 3, and are divided in two groups according to the type of porous ceramic preform used for glass infiltration: aluminaAl 2 O 3 (A1 to A3), or spinel-MgAl 2 O 4 (S1 to S5). The reported infiltration temperatures are also indicated in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…Viscosity determines the temperatures at which the processing Table 3 Compositions (mol%) of glasses used for infiltration of porous preform of alumina -Al 2 O 3 (A1 to A3) and spinel -MgAl 2 O 4 (S1 to S5), and respective temperature of infiltration (T), from literature [34][35][36][37]. techniques of glasses will occur, like melting, forming, annealing, thermal tempering, and ion-exchange [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…1 shows the calculated viscosities from the chemistry of some glasses as a function of the temperature used for the infiltration process reported in Refs. [15][16][17]. It could be observed that the viscosities of the glasses at the infiltration temperature ranged from around 10 2 to 10 3 dPa s. Therefore, in this work it was established that the glass should have viscosity lower than 10 2 dPa s at 1200 • C for the design of glass composition.…”
Section: Simulation Of Glass Properties and Compositional Designmentioning
confidence: 95%
“…Light scattering significantly decreases total light transmittance through the material [8]. In addition, residual porosity significantly reduces the mechanical properties of the biocomposite, [5] and is considered the most significant optical heterogeneity in its microstructure, causing significant light scattering and therefore decreasing light transmittance [8].…”
Section: Introductionmentioning
confidence: 99%
“…Good aesthetics for artificial teeth can be obtained using glass-infiltrated alumina biocomposites, which can be translucent enough to mimic the characteristics of the natural teeth, [3] yet keeping an excellent, accurate marginal and internal adaptation after multiple heat treatments [4]. The good marginal adaption of these glass-infiltrated alumina biocomposites is related to the low shrinkage of the final material, [5] which is below 0.5%, due to the fact that pre-sintering of the preform and infiltration of the glass are performed at relatively low temperatures [6].…”
Section: Introductionmentioning
confidence: 99%